KARAKTERISTIK KONDISI RUMEN SAPI PESISIR SELATAN DENGAN RANSUM JERAMI PADI AMONIASI UREA - Dewi Febrina (Jurnal Peternakan, 2006)
Charakteristics of rumen condition were measured in a total of 4 local cattle (pesisir Selatan) with an average initial body weight of 109 ± 12.9 kg. The animals were randomly allocated according to a 4 x 4 Latin Square Design to· the following experimental diets : 20% concentrate + 80% ammonia-treated rice straw (ARS) (ration A), 40% concentrate + 60% ammonia-treated rice straw (ARS) (ration 8), 60% concentrate + 40% ammoruatreated rice straw (ARS) (ration q and 80% Concentrate + 20% ammonia-treated rice straw (ARS) (ration D). Crude protein of the rations ranged from 9.4%to 14.2%, while the TON content ranged from 53.7% to 66.3%.The result showed that pH, NJ-h-N and VFA were significantly affected (p< 0.(5) by ratiOns, (factor A) while VFA and pH were significantly affected (P< 0.05) by time's observations (factor 8) bUt didn't attect(P> 0.05) NH3-N concentration.